Towards the construction of representative regional hydro(geo)logical numerical models: Modelling the upper Danube basin as a starting point - Pujades, Estanislao; Kumar, Rohini; Houben, Timo; Jing, Miao; Rakovec, Oldrich; Kalbacher, Thomas; Attinger, Sabine (Frontiers in Earth Science, 2023)
Pressure on groundwater resources is increasing rapidly by population growth and climate change effects. Thus, it is urgent to quantify their availability and determine their dynamics at global scale to assess the impacts of global climate or anthropogenically induced pressure and design global/worldwide management strategies. In this context, hydrogeological numerical models become essential to reproduce and estimate the behavior of groundwater resources. Existing parametrization approaches proposed to assign parameters to regional hydrogeological models mainly rely on groundwater head data. Steady state piezometric head data are typically used to infer local hydraulic transmissivities and transient data for estimating storativity values. In this work, the German portion of the Upper Danube Basin is modeled to demonstrate the main difficulties of this approach when used for the parametrization of regional hydrogeological models and to develop an alternative approach. The hydrogeological model of the Danube consists of the groundwater finite element code OpenGeoSys forced by the groundwater recharge of the surface hydrological model mHM. The main novelties are (1) the use of an alternative methodology based on spectral analyses of the river baseflow and a steady state calibration taking as reference the topography to constraint the hydraulic parameters and facilitate the calibration process, and (2), the calibration of the hydraulic parameters from the transient state model by considering statistic parameters derived from the piezometric head evolution. The results show that the proposed methodology is useful to build representative large scale groundwater models. The proposed methodology is finally compared with standard approaches proposed by other authors for the construction of regional models. The comparison shows that the proposed approach allows obtaining more reliable results, especially in mountainous areas.